Edpuzzle Application Training for Mandarin Language Teachers in Malang City as an Effort to Support Digital Learning in the Era of Society 5.0 - Aiga Ventivani; Lukluk Ul Muyassaroh; Amira Eza Febrian Putri (Journal of Chinese Language and Culture Studies, 2024)
The Society 5.0 era emphasizes collaboration between humans as its center and technology as its basis. The use of technology can be utilized in overcoming problems in the teaching and learning process. The problem currently being faced is the lack of variation in digital learning media. Currently, Mandarin teachers rely more on handouts that are made independently. This is because the preparation of handouts is considered the most feasible to be prepared. In addition to using handouts, information was also obtained that Mandarin teachers like to use YouTube accounts as an alternative digital-based teaching media compared to other teaching resources. This is because YouTube videos are the easiest to access even though there are several shortcomings such as there are always advertisements, students can skip them and the duration is too long. As a result, teachers feel more confident and ready to implement more effective digital learning methods in their classrooms. In other words, this activity succeeded in providing an in-depth understanding of the use of technology in learning, despite the technical and access constraints faced by Chinese teachers. Through this training, the teachers not only gained new technical skills but also strategies to overcome the challenges. As a suggestion, further training and ongoing technical support should be organized to ensure teachers can continue to develop their digital competencies.